2010
DOI: 10.1177/0971890720100103
|View full text |Cite
|
Sign up to set email alerts
|

Equity Investment Decisions: Are Demographic Variables Really Significant?

Abstract: The objective of the present study is to find out the impact of demographic variables on the equity share investment decisions of the employees. The study is done on the employees of Oil India Limited [OIL]. It is found that out of the four demographic variables namely age, gender, qualification and designation considered for the study only age is having significant influence on the equity share investment decisions in past, present and future however, gender is only having impact on the present equity investm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…It means that the older age of a person the more profitable investment decision he makes. This result is in line with Singh (2010), that states the older the age of a person, the more avoidance of risk in making investment decisions, and vice versa. This happens because as we get older the knowledge and experience that a person has in making the decision is also getting higher.…”
Section: Hypothesis Testingsupporting
confidence: 86%
See 1 more Smart Citation
“…It means that the older age of a person the more profitable investment decision he makes. This result is in line with Singh (2010), that states the older the age of a person, the more avoidance of risk in making investment decisions, and vice versa. This happens because as we get older the knowledge and experience that a person has in making the decision is also getting higher.…”
Section: Hypothesis Testingsupporting
confidence: 86%
“…Growing age will cause different ways of thinking which then will be manifested in human behavior including in determining investment decisions. Singh (2010), states that the older the age of a person, the more avoidance of risk in making investment decisions, and vice versa. This happens because as we get older the knowledge and experience that a person has in making the decision is also getting higher.…”
Section: Age Affects Investment Decisionmentioning
confidence: 99%
“…Age and education are seen as significant factors and are consistent with other studies where similar findings were derived (Singh & Bhattacharjee, 2010a). Young and educated people are less likely to be excluded than older and less educated members (Johnson & Nino-Zarazua, 2007).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 90%
“…Ordinal logistic regression is used to predict the output with one or more independent variables (predictor variable) when the dependent variable is in the ordinal scale. Singh and Bhattacharjee (2010a) and Singh and Bhattacharjee (2010b) have sued similar analysis to draw the analogy.…”
Section: Impact Of These Factors On Financial Inclusionmentioning
confidence: 94%
“…Richards et al, (2017) find evidence that men are more likely to hold losses longer because of that they are more willing to the disposition effect than women. Singh & Bhattacharjee (2010a) found that gender has a significant role to play in equity investing.…”
Section: Tax-loss Selling (Tls)mentioning
confidence: 99%